Parallel Processing in a Multifeature Whole-Report Paradigm. - Kyllingsbæk, Søren; Bundesen, Claus (Journal of Experimental Psychology. Human Perception & Performance, 2007)
Observers given brief exposures of pairs of colored bars and asked to report both the color and the orientation of each bar showed evidence of stochastic independence between reports of the 4 features (2 colors and 2 orientations). The authors also found virtually perfect stochastic independence between reports of colors and directions of motion of pairwise presented circular disks at each of 3 levels of exposure duration that varied unpredictably from trial to trial. Stimulus triples, rather than pairs, yielded more complex results. However, the findings provide strong evidence that the relevant features of the 2-3 stimuli were identified and localized in parallel across the display. Reprinted by permission of the publisher.